Insight into Market Supply and Demand of Private Forests in Croatia - Beljan, Karlo (Array, 2021)
Due to their modest 23% share, private forests in Croatia are a resource that is perceived as less important than state-owned forests. One of the basic characteristics of private forests is fragmentation, which is also the biggest obstacle to a successful and, economically speaking, sustainable management of private forests. The cases in which a private forest with its area and integrity can generate a sustainable economic income to its owner are not common. However, from an economic point of view, private forests still have one advantage. Unlike state-owned forests, private forests can be the subject of investment and change hands. Based on this, this paper investigates the supply of private forests on the free market. For private forests that were publicly put for sale in the period from 2010 to 2020, their spatial-temporal distribution and supply dynamics and trends (price and quantity) were analyzed. The data were collected from the leading real estate advertising platform in Croatia (Njuškalo.hr), and a total of 866 advertisements were analyzed, relating exclusively to the sale of raw wood material along with the accompanying forest land. On the other hand, in order to assess the demand, data were collected on the number of potential buyers who viewed the advertisements (period 2020-2021). In the observed ten-year period, a total of 1,890.63 ha of private forests with a total asking value of €32.14 million were offered on the market. The share of advertisements advertised through real estate agencies is 42.1%. The average total annual supply is 170 ha and has a growing trend (in the advertisements in the coastal part of Croatia, the average area is 1.3 ha, while the average area in the continental part is 3 ha). The prices are not constant but rising. According to compound interest, the price increase in the coastal area is 1.57% and 7.49% in the continental area. From the relationship between supply and demand or, more precisely, the relationship between